Evaluation of hyperspectral imaging as a modern aid in clinical assessment of burn wounds of the upper extremity - Promny, Dominik; Aich, Juliane; Pueski, Tamas; Edo, Alejandro Marti; Reichert, Bert; Billner, Moritz (Burns, 2022)
The most common burn wound assessment continues to be the clinical inspection and the tactile examination, which are subjective and remain challenging even for experienced burn surgeons. Recently, hyperspectral imaging camera systems have been increasingly used to support the evaluation of burn wounds. The aim of our study was to determine if hyperspectral imaging analysis differentiates and objectifies the assessment of burn wounds in burns of the upper extremities.
CRIS-Team WoS Importer:2022-08-12